Impact of the removal of Amazon Forest on the Southern Hemisphere storm tracks in future climate - Philipp Edson Dias da Silva (2019)
The Amazon Forest is one of the most important ecosystems in the world. The forest plays an important role in the global hydrological system. Deforestation affects evapotranspiration, latent heat, river discharges and, consequently, the global climate. In this study, HadGEM2-ES Earth system model is used to investigate the impact of the removal of the Amazon Forest on the storm tracks (STs) of the (HS) in future climate. Firstly, the recent past climate simulated by HadGEM2-ES is compared to that indicated by the Era-Interim reanalysis to evaluate the performance of the model in representing the STs in the HS. Next, experiments with and without the Amazon Forest under two future scenarios Representative Concentration Pathways (RCP) are contrasted against controlled experiments to examine possible future changes in STs. The HadGEM2-ES has the ability to simulate well the midlatitude storm tracks in the Southern Hemisphere (SH). However, the model tends to represent the austral winter ST position with an equatorward bias and a zonal bias in the spiral towards the pole. The main differences are found during the austral winter and spring, with large track density biases over the Indian Ocean indicating a poor representation of the ST in this specific region. This seems to be related to two factors. First, the large negative genesis biases over South America, Antarctic Peninsula and the Antarctic coast. Second, the model resolution and the representation of the Andes Mountains in South America. The model generally underestimates the extratropical cyclone intensity, which in part is related to low spatial resolution. The future projections show a consistent shift of the STs in the HS toward the pole, and this is reduced when the Amazon Forest is removed. The storm track changes under the RCP4.5 are larger than in the RCP8.5 scenario. In general, the changes are strongly associated with the mean large-scale circulation, although the change in the Amazon Forest is on a regional-scale. When the Amazon Forest is removed, the temperature decreases over northern South America. There is also a decrease in the total number of cyclones in the SH and a slight shift of cyclone intensity distributions toward stronger storms.